KUALITAS PRODUK DAN KEPUTUSAN PEMBELIAN: PERAN BIAYA PEMASARAN SEBAGAI PEMODERASI - Suhadarliyah Suhadarliyah; Dahlia Amelia; Ronald Tehupuring (Proceeding Maritime Business Management Conference, 2023)
The aim of this study is to test and analyze the influence of product quality on purchasing decisions which is moderated by marketing costs. The sample for this study uses food and staple retailing listed on the Indonesia Stock Exchange for the 2019-2022 period, while the analysis year used to test the hypothesis is the 2020-2022 period. This study uses a panel data regression approach with the help of eviews version 13. The results of this study find that product quality has a positive and significant effect on purchasing decisions, while marketing costs cannot strengthen the influence of product quality on purchasing decisions. This study contributes to future studies because it fills the void of previous studies which have not used secondary data approaches to measure product quality and purchasing decisions